Economics, the environment and our common wealth - Boyce, James K.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2013)
Comprising a decade's worth of essays written since the publication of the author's pathbreaking book, The Political Economy of the Environment (2002), this volume discusses a number of diverse environmental issues through an economist's lens. Topics covered include environmental justice, disaster response, globalization and the environment, industrial toxins and other pollutants, cap-and-dividend climate policies, and agricultural biodiversity.
1. The environment as our common heritage -- 2. Is inequality bad for the environment? -- 3. In the wake of the storm : disasters and environmental justice -- 4. Justice in the air : tracking america's industrial toxics -- 5. Where credit is due -- 6. Cap and dividend : carbon revenue as common wealth -- 7. A Chinese sky trust -- 8. A future for small farms -- 9. Globalization and our environmental future.
Includes bibliographical references and indexes.
Keywords: Environmental economics; Electronic books